Integrating Language and Spirituality: The Impact of Instructor Mentoring and Foreign Language Habituation on Santri Intelligence Development in Indonesian Islamic Boarding Schools - Fariha, Hanik Sindi; Khoirotul Idawati; Hanifuddin (Papanda Publisher, 2025)
Introduction: Language education in Islamic boarding schools (pesantren) presents unique opportunities to integrate linguistic competence with spiritual development. This study investigated how language instructor mentoring utilizing foreign language habituation approaches enhances santri's spiritual and linguistic intelligence at Pesantren Sains Tebuireng. Methods: A qualitative descriptive design was employed with purposively selected participants including the chief administrator, language instructors, student language administrators, and santri. Data were collected through semi-structured interviews, systematic observations, and document analysis, then analyzed using data reduction, display, and conclusion drawing procedures. Trustworthiness was established through triangulation, observation persistence, and peer debriefing. Results: Findings revealed that instructors functioned as multidimensional mentors—serving as teachers, spiritual guides, and role models—implementing systematic habituation strategies including vocabulary enrichment, multimedia learning, and performance activities. The tiered mentoring system, where instructors mentored student administrators who subsequently guided peers, effectively developed linguistic competencies across four language skills while fostering Islamic values of sincerity, perseverance, and knowledge pursuit. Supporting factors included instructor authority, collaborative structures, and accountability mechanisms, while motivational fluctuations, scheduling challenges, and incomplete immersion emerged as inhibiting factors Discussion: The study extends multiple intelligences theory and social learning frameworks by demonstrating specific mechanisms linking language instruction with spiritual development, providing practical implications for pesantren seeking to balance religious education with linguistic competence development.